Real and perceived impacts of blasting at Teberebie Goldfields Limited - Agra, Gotthold Yawo (2011)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of Master of Philosophy degree in Mining Engineering, 2001